SOCIAL EMOTIONAL LEARNING (SEL) TERINTEGRASI PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR ISLAM MANAARATUL IMAN BANDUNG - Mohammad Dzakiyyuddin; Anton Musa; Mohammad Irham; Tuti Alawiyah; Ansori (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted due to the discovery of an elementary schools that has integrated the SEL (Social Emotional Learning) approach into its PAI program. (Pendidikan Agama Islam). The purpose of this research is to describe and discuss how the school integrates SEL with Islamic Religious Education, what the obstacles and solutions are, and what the outcomes are. This research uses a qualitative approach with a case study method. Data collection used observation techniques, interviews, and documentation studies. This research reveals that SEL has been integrated by incorporating it as an approach within the framework of the PAI curriculum, and establishing it as a standard for Islamic interaction and behavior in the school environment; obstacles were found in the limited competence of teachers and the lack of synergy among all school elements; solutions include teacher training, parental involvement, partnerships with the community, and evaluation and enhancement by scholars and psychologists brought into the school. The study's results conclude that the school being researched has integrated SEL with Islamic Religious Education, conducted educational processes that stimulate social-emotional skills, and created a more inclusive and supportive learning environment, thereby better supporting students' academic achievements.